The Spatial Factor in African History : The Relationship of the Social, Material, and Perceptual - Howard, Allen Marvin,; Shain, Richard Matthew, (African Social Studies Series ;, 2005)
The authors of this inter-disciplinary collection examine the role of space in six areas of West, Central and East Africa during the nineteenth and twentieth centuries. They demonstrate the active quality of space and analyze the ways in which people have contested and shaped space, including responses to crises. In addition, a lengthy essay re-interprets tropical African history, 1800-1930, using spatial theory. Contributors look at how people have constructed mental maps, used discourse to organize territories, and perceived social landscapes. The studies employ a tri-level approach, one that moves from specific places to regions to macro-regional or transnational systems and back again. Authors draw upon written and oral sources to reconstruct the past and employ innovative mapping techniques to illustrate spatial dynamics.